OCCIPITAL LOBE SYNDROME - Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2016)
The ability to recognize objects and words is not just depend on the integrity of visual pathway andÂ  primary vision area on cerebral cortex (Brodmann area 17), but also secondary vision area 18 and tertiary vision area 19 on occipital lobe. Lesion in occipital lobe could disturb of human visual function such as visual field defects, inability to recognize colors, inability to recognize words, visual hallucinations and illusions, occipital lobe epilepsy, and Antonâ€™s syndrome. Some causes of occipital lobe lesion are head trauma, chemical intoxicity, neoplasma, stroke, degenerative disease, and vascular disease. Prognosis of occipital lobe syndrome is depend on the initial condition but prognosis from the majority of cases with occipital lobe lesions is not good because the exact intervention is not discovered yet and included one ofirreversible disease.